1995
DOI: 10.2307/591851
|View full text |Cite
|
Sign up to set email alerts
|

Religious Identification and Moral Attitudes: The British Case

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Wiley-Blackwell andThe London School of Economics and Political Science are collaborating with JSTOR to digitize, preserve and extend access to The British Journal of Sociolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…The variable that has drawn the most attention is participant sex. The finding that men's attitudes are less favorable than women's is parsimonious (Hayes, 1995;Larsen et al, 1980;Steffens, in press). When target sex is specified, men's attitudes toward gay men also are more unfavorable than women's (for a review, see Kite & Whitley, 1996).…”
Section: Predictors Of Attitudes Toward Lesbians and Gay Menmentioning
confidence: 86%
“…The variable that has drawn the most attention is participant sex. The finding that men's attitudes are less favorable than women's is parsimonious (Hayes, 1995;Larsen et al, 1980;Steffens, in press). When target sex is specified, men's attitudes toward gay men also are more unfavorable than women's (for a review, see Kite & Whitley, 1996).…”
Section: Predictors Of Attitudes Toward Lesbians and Gay Menmentioning
confidence: 86%
“…Earlier research also found that the religiously-affiliated were more likely to hold socially-conservative opinions on similar moral questions, compared to the unaffiliated (Hayes 1995).…”
Section: Existing Research On the "Religious Nones"mentioning
confidence: 90%
“…Considering the fact that a conservative attitude in discussing sexual matters among family members is apparent in Turkish families (Eksi 1982;Necef 1999), it is reasonable to expect that Turkish parents and their children will differ considerably in their attitudes toward lesbians and gay men. Furthermore, previous research has consistently determined that younger age cohorts are typically more tolerant of homosexuality than those from older age cohorts (Hayes 1995;Jensen et al 1998). Based on the previous research, the same pattern is expected to be observed in the current sample.…”
Section: Introductionmentioning
confidence: 96%